(untitled) (Bangladesh Medical Journal, 2023)
The healthcare professionals endured a major physical as well as psychological burden against the coronavirus disease (COVID-19) global catastrophe. Owing to their role in the frontline, they were the most exposed group who faced the deadly virus head-on which increased their mental health problems during this pandemic. The study was designed as a cross-sectional study to assess the prevalence of PTSD among 314 working physicians from the purposively selected government and private hospitals during the COVID-19 pandemic in Dhaka city. ‘Impact of Event Scale-Revised’ (IES-R) was used to construct the questionnaire. The mean age of the physician was 32.2±4.7 years. One-fifth of them (21.0%) diagnosed COVID-19 positive by the rt-PCR test. The most prevalent co-morbidities were found bronchial asthma (74.2%), hypertension (32.3%) and diabetes mellitus (19.4%). About half of the physicians (48.6%) had mild PTSD. The test of significance denotes the significant associations of the prevalence of mild PTSD level with physician’s age, gender, marital state, work settings, results of COVID-19 positive and had co-morbidities in physicians (p<0.05). The prevalence of mild PTSD was higher in the age group of 25-35 years (49.1%), in females (49.8%), unmarried (50.0%), work in private settings (51.5%), ever been COVID-19 positive (59.1%) and had co-morbidities (51.6%). This study reveals that about half the physicians are suffering from mild PTSD. A high encumbrance of COVID-19 related mental disorders and fear among frontline physicians’ entreaties to government and policymakers’ prompt regard for taking appropriate preventive measures. Bangladesh Med J. 2021 Sept; 51(1): 52-58